Patient-specific biodegradable implant in pediatric craniofacial surgery. Issue 2 (February 2017) - Essig, H.; Lindhorst, D.; Gander, T.; Schumann, P.; Könü, D.; Altermatt, S.; Rücker, M.
Abstract: Surgical correction of premature fusion of calvarial sutures involving the fronto-orbital region can be challenging due to the demanding three-dimensional (3D) anatomy. If fronto-orbital advancement (FOA) is necessary, surgery is typically performed using resorbable plates and screws that are bent manually intraoperatively. A new approach using individually manufactured resorbable implants (KLS Martin Group, Tuttlingen, Germany) is presented in the current paper. Preoperative CT scan data were processed in iPlan (ver. 3.0.5; Brainlab, Feldkirchen, Germany) to generate a 3D reconstruction. Virtual osteotomies and simulation of the ideal outer contour with reassembled bony segments were performed. Digital planning was transferred with a cutting guide, and an individually manufactured resorbable implant was used for rigid fixation. A resorbable patient-specific implant (Resorb X-PSI) allows precise surgery for FOA in craniosynostosis using a complete digital workflow and should be considered superior to manually bent resorbable plates.